Egg Quality Characteristics Of Emu (Dromaius Novaehollandiae) - Murugan, M.; Gnanaraj, P.Tensing; Sivakumar , T. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Commercial emu farming is an upcoming business avocation in India. Emu is mainly reared for its oil and meat, however in emu breeding farms, producing cost effective day old emu chick is a principal activity which decides the profitability of breeder as well commercial emu farms. Hatchability plays a major role in deciding the cost of production of day old emu chick. A preliminary study on production performance of EMU breeders was carried out by Boopati et al. (2012) .To evolve suitable package of practices for emu incubation in tropical regions, we are in need of basic understanding about the quality characteristics of emu egg..Keeping in mind, an experiment was designed to study the external and internal quality characteristics of emu egg in tropical region.